Characteristics of daily rainfall over the Maritime Continent - Suaydhi Suaydhi (Faculty of Science and Mathematics, Universitas Kristen Satya Wacana, 2018)
Daily rainfall characteristics is important in the anticipation of natural hazard events, such as floods and landslides. In this study, daily rainfall data from the Global Precipitation Climatology Project One Degree Daily (GPCP1DD) dataset are used to analyze the rainfall frequency, intensity and extreme rainfall indicators over the Indonesian Maritime Continent. A threshold of 1 mm is used to define a wet day. The analysis is conducted over the whole domain and several sub domains. It is revealed that the rainfall patterns over Indonesia are shaped by the frequency distribution of rainfall intensity over different seasons. Heavy rainfall (greater than 15 mm/day) generally determines the rainfall peak season over a specific region. It is also shown that the land areas receive more frequent and more intense rainfall than the ocean areas.